A Cation and Anion Dual Doping Strategy for the Elevation of Titanium Redox Potential for High‐Power Sodium‐Ion Batteries. Issue 29 (12th May 2020) - Chen, Mingzhe; Xiao, Jin; Hua, Weibo; Hu, Zhe; Wang, Wanlin; Gu, Qinfen; Tang, Yuxin; Chou, Shu‐Lei; Liu, Hua‐Kun; Dou, Shi‐Xue
Abstract: Titanium‐based polyanions have been intensively investigated for sodium‐ion batteries owing to their superior structural stability and thermal safety. However, their low working potential hindered further applications. Now, a cation and anion dual doping strategy is used to boost the redox potential of Ti‐based cathodes of Na3 Ti0.5 V0.5 (PO3 )3 N as a new cathode material for sodium ion batteries. Both the Ti 3+ /Ti 4+ and V 3+ /V 4+ redox couples are reversibly accessed, leading to two distinctive voltage platforms at ca. 3.3 V and ca. 3.8 V, respectively. The remarkably improved cycling stability (86.3 %, 3000 cycles) can be ascribed to the near‐zero volume strain in this unusual cubic symmetry, which has been demonstrated by in situ synchrotron‐based X‐ray diffraction. First‐principles calculations reveal its well‐interconnected 3D Na diffusion pathways with low energy barriers, and the two‐sodium‐extracted intermediate NaTi0.5 V0.5 (PO3 )3 N is also a stable phase according to formation energy calculations. Abstract : Giving Ti polyanions a lift : The working voltage of a Ti‐based polyanion with unusual cubic symmetry and zero‐strain property is elevated effectively by using a cation/anion dual doping strategy. The composite electrodes enable a long‐term cycling stability, outstanding rate performance, and unique 3D sodium diffusion channels.